2020
DOI: 10.1007/s13158-020-00276-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Preservice Teachers for Technology and Digital Media Integration: Implications for Early Childhood Teacher Education Programs

Abstract: Technology and digital media are now embedded in children's daily lives and can have significant impact on children's early development and learning. Preparing early childhood teachers to integrate a variety of technologies into classroom practices can be challenging. This study explores perceptions of preservice teachers about technology integration into their educational programs and assesses their satisfaction with such preparation. A total of 192 preservice teachers participated in this study. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Studies on teachers" learning on the use of ICT (e.g. Alelaimat et al, 2020;Ciptaningrum, 2018;Yet & Noordin, 2017) conclude that ICT Professional Development (PD) for teachers comprise of standardize, one-size-fit all programs that show teachers how to use the technology hardware and software. Pre-service teachers at the English Language and Education Depart-ment at this university in Yogyakarta, have received training on how to use an online learning management system for learning purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on teachers" learning on the use of ICT (e.g. Alelaimat et al, 2020;Ciptaningrum, 2018;Yet & Noordin, 2017) conclude that ICT Professional Development (PD) for teachers comprise of standardize, one-size-fit all programs that show teachers how to use the technology hardware and software. Pre-service teachers at the English Language and Education Depart-ment at this university in Yogyakarta, have received training on how to use an online learning management system for learning purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of regular everyday indoor–outdoor activities in preschool contexts leaves little or no scope for using digital technology tools for pedagogical purposes, for example, in Norway only in 1% cases digital tools were observed to be used in teaching amidst various other indoor–outdoor activities (Kallestad & Ødegaard, 2013 ). Alelaimat et al ( 2020 ) reported that early childhood educators feel less prepared to use digital technology in their teaching practice. Not all but in some preschools in Australia, Norway and Singapore, one of the major use of digital tools for educators is mostly for communicating children’s daily reflections and informing individual child development with parents through some digital portals.…”
Section: Early Childhood Education Across the Five Countriesmentioning
confidence: 99%
“…According to Jalongo ( 2021 ), in the early childhood context where most programmes follow children’s interest based philosophies, a 360 shift to remote learning has totally changed the early years teaching–learning context. A number of studies highlight the need to include new content on improving technology skills and use of technology in teacher education programs to prepare better early childhood teachers to deliver programs in future crisis conditions (Alelaimat et al, 2020 ; Jalongo, 2021 ).…”
Section: Early Childhood Education Across the Five Countriesmentioning
confidence: 99%
“…Barriers to technology integration are universally researched. For example, failure to perceive the usefulness of technologies (Lee & Lehto, 2013;Teo, 2011), a lack of training and support (Derfler, 2002;Makki et al, 2018), and a lack of teacher knowledge (Alelaimat et al, 2021;Mumtaz, 2000;Ward & Parr, 2010) account for teachers' reluctance to technology-driven teaching. Those confirmed barriers behind technology adoption include three major groups: technology itself (e.g., perceived usefulness, perceived ease of use), external factors (e.g., class preparation time, access to technology), and internal factors (e.g., knowledge and skills, attitudes and beliefs) (Ertmer, 1999;Hew & Brush, 2007;Reyneke, 2020).…”
Section: Importance Of the Problemmentioning
confidence: 99%